The effect of technology choice on automobile assembly plant productivity - Van Biesebroeck, Johannes (Economic & Social Studies, 2002)
Productivity growth is usually represented by a continuous shift of the production or cost function. In the automobile industry, there is evidence of a more discrete change in the technology. I estimate a structural model of production and technology choice, using a panel of US automobile assembly plants from 1963 to 1996. New decomposition results suggest that plant-level changes, as opposed to compositional effects, are the most important determinant of aggregate productivity growth.
Keywords: Technology; Automobile industry; Productivity; Assembly plants